Test the effectiveness of transactional and transformational leadership in the Egyptian Environment - سليم احمد عبد السلام (Journal of Economics and Administrative Sciences, 2013)
The present study aims to test a range of hypotheses about the effectiveness of each of the theory of transactional leadership, and the theory of transformational leadership in the Egyptian environment, and to identify any of them are better able to predict the effectiveness of leadership. And after the effect will be to identify the quality of the relationship between the leader and the subordinate in leadership , and what is the role of transformational leadership dimensions influencing the effectiveness of leadership. The field study was conducted on a sample of companies’ public and private sector and the government in Egypt. The results of the study resulted in experimental that transactional leadership was having a significant impact on the effectiveness of the commander expressed satisfaction from work, and the performance of the functional roles. The results also found that transformational leader is the one, who formulate a vision for the future of the organization, and provides a model to emulate subordinates, and works to accelerate the acceptance of the goals of the group, and provides individual support. In turn, this leads to increase the effectiveness of the commander expressed consent of the workers. The results of the study also found that the transformational leader who is developing the objectives of the working group, and draws high expectations for performance, reflected in the form of effective leadership, and improve the level of performance of employees for their roles, and provide performance levels beyond the minimum set by the organization. On the other hand, the results showed that the leadership of transactional was more effective than transformational leadership in the interpretation expressed satisfaction with the work, while transformational leadership was more effective than transactional leadership expressed in the performance of the index job role. The study group implications for researchers and managers, the study also suggested a range of ideas for future studies.